Effect of boiling and roasting on the fermentation of soybeans into dawadawa (soy-dawadawa) - Darkwa, S.; Sakyi-Dawson, E.; Diako, C.; Annan, N.T.; Amoa-Awua, W.K. (International Journal of Food Microbiology, 2005)
Soybeans which had initially been dehulled by either boiling (boiled/dehulled) or roasting (roasted/dehulled) before peeling, were cooked and fermented into dawadawa, a traditional food condiment. The micropopulation, enzymatic activities, proximate composition, amino acid, and aroma profiles of the two types of soybean dawadawa were evaluated during fermentation. Only minor differences were found in the microbial profiles of the two types of soy-dawadawa. Although boiled/dehulled soy-dawadawa initially had lower microbial counts, it recorded higher counts at the advanced stages of fermentation. Proteolytic and amylolytic Bacillus species including Bacillus subtilis, Bacillus pumilus, Bacillus licheniformis, Bacillus cereus, and Bacillus firmus dominated the micropopulation of the two types of soy-dawadawa with Bacillus subtilis accounting for about 50% of the Bacillus species in all samples. Lactic acid bacteria and yeasts occurred in low numbers in the two types of soy-dawadawa. The proximate composition of the two types of soy-dawadawa were similar, and their contents of moisture and protein increased whilst fat and ash decreased during fermentation. Both types of fermenting soy-dawadawa recorded similar levels of α-amylase activity, but boiled/dehulled soy-dawadawa showed slightly higher protease activity. The levels of isoleucine, leucine, lysine, phenylalanine, arginine and proline increased significantly with fermentation time in both types of soy-dawadawa. With respect to differences in their aroma profiles, hexanodecanol, octadecyl acetate, 1,2-dimethyl benzene, tetradecene, (E)-5-eicosene, cyclohexadecane, and hexacosane were found only in the roasted/dehulled samples, whilst 1,2-ethanediol, ethyl acetate, dimethyl disulfide, cyclotetradecane, decene, indole , 2 butyl-octenal, acetophenone, and toluene were found only in the boiled/dehulled samples. A market focus group showed preference for roasted/dehulled soy-dawadawa over boiled/dehulled soy-dawadawa. Apart from the volatile aroma compounds, the biochemical and microbiological profiles of the two types of soy-dawadawa showed only minor differences and were also similar to the profiles reported for African locust bean dawadawa. © 2005 Elsevier B.V. All rights reserved.
Keywords: Bacillus species; Dawadawa; Fermentation; Soy-dawadawa; Soybeans